Determination of muscle differentiation markers SMA and MSA in CD117-positive and CD117-negative gastrointestinal stromal tumors of different malignant potential - I. S. Shpon’ka; V. R. Yakovenko (Patologìâ)
Aim. To determinate the muscle differentiation markers SMA and MSA in CD117-positive and CD117-negative gastrointestinal stromal tumors of different malignant potential.